Ginsenosides ameliorates high altitude-induced hypoxia injury in lung and kidney tissues by regulating PHD2/HIF-1α/EPO signaling pathway - Ji, Peng; Zhang, Zepeng; Mingyao, E.; Liu, Qing; Qi, Hongyu; Hou, Tong; Zhao, Daqing; Li, Xiangyan (Frontiers in Pharmacology, 2024)
Background: The primary constituent of ginseng, known as ginsenosides (GS), has been scientifically demonstrated to possess anti-fatigue, anti-hypoxia, antiinflammatory, and antioxidant properties. However, the effect and mechanisms of GS on tissue injury induced by high-altitude hypoxia still remain unclear.This study aims to investigate the protective effect of GS on a highaltitude hypoxia model and explore its mechanism.Materials and methods: Sprague-Dawley rats were placed in a high-altitude simulation chamber for 48 hours (equivalent to an altitude of 6,000 meters) to establish a high-altitude hypoxia model. We assessed the anti-hypoxic efficacy of GS through blood gas analysis, complete blood count, and hemorheology analysis. We used H&E and hypoxia probe assays to evaluate the protective effect of GS on organ ischemiainduced injury. Further, we used ELISA and qPCR analysis to detect the levels of inflammatory factors and oxidative stress markers. Immunohistochemistry and immunofluorescence staining were performed to determinate protein expression of hypoxia inducible factor 1-alpha (HIF-1α), erythropoietin (EPO), and prolyl hydroxylase 2 (PHD2).In the survival experiment of anoxic mice, 100mg/kg of GS had the best antianoxic effect. GS slowed down the weight loss rate of rats in hypoxic environment. In the fluorescence detection of hypoxia, GS reduced the fluorescence signal value of lung and kidney tissue and alleviated the hypoxia state of tissue. Meanwhile GS improved blood biochemical and hematological parameters. We also observed that GS treatment significantly decreased oxidative stress damage in lung and kidney tissues. Further, the levels of inflammatory factors, IL-1β, IL-6, and TNF-α were reduced by GS. Finally, GS regulated the PHD2/HIF-1α/EPO signaling pathway to improve blood viscosity and tissue hyperemia damage.GS could alleviate high-altitude induced lung and kidney damage by reducing the level of inflammation and oxidative stress, improving blood circulation through the PHD2/HIF-1α/EPO pathway.